Processing and characterisation of BaZr0.8Y0.2O3−δ proton conductor densified at 1200 °C. Issue 8 (3rd February 2022) - Triviño-Peláez, Ángel; Pérez-Coll, Domingo; Aparicio, Mario; Fagg, Duncan P.; Mosa, Jadra; Mather, Glenn C.
Abstract : BaZr0.8 Y0.2 O3− δ densifies at 1200 °C on employing a combination of Ba excess, ZnO sintering additive and nanopowders prepared by a sol–gel route. The low densification temperature decreases grain-boundary resistance despite the lower grain size. Abstract : Barium zirconate-based perovskites (BZY) are intensely studied proton conductors for high-temperature electrochemical applications; however, their refractory nature means excessive temperatures are required for sintering (∼1700 °C). Although different strategies have been employed to improve densification, a high-temperature step (1300–1700 °C) is generally required to achieve sufficient grain growth and good electrical properties. Here, sol–gel synthesis using alkoxide precursors is employed to obtain BaZr0.8 Y0.2 O3− δ sinter-reactive powders with Ba excess at 750 °C. High relative densities (∼98%) of ceramic bodies with an average grain size ∼190 nm were obtained on sintering isostatically-pressed pellets at the uniquely low temperature of 1200 °C for 4 hours on addition of 4% mol ZnO as a sintering agent to the Ba-excess sol–gel powders. Impedance spectroscopy indicates that the resistance of the greater grain-boundary volume arising from the low densification temperature is largely offset by a higher specific grain-boundary conductivity than that of the same composition sintered at 1650 °C with larger grain size. Conductivity measurements for prolonged periods in dry and wet ( p H2O ∼ 0.022 atm) 90% N2 : 10% H2 and 90% Ar : 10% CO2 atmospheres at 500 °C verified that Ba excess in the starting composition did not contribute to deteriorating chemical stability. Processing of sol–gel BZY nanopowders with Ba excess combined with ZnO sintering aid is thus demonstrated as a successful low-temperature route for obtaining BZY with high density, stability and sufficient grain growth for electrochemical applications.